They ask, you answer : a revolutionary approach to inbound sales, content marketing, and today's digital consumer, revised & updated - Sheridan, Marcus (Gildan Audio, 2019)
In today's digital age, the traditional sales funnel-marketing at the top, sales in the middle, customer service at the bottom-is no longer effective. To be successful, businesses must obsess over the questions, concerns, and problems their buyers have, and address them as honestly and as thoroughly as possible. Every day, buyers turn to search engines to ask billions of questions. Having the answers they need can attract thousands of potential buyers to your company-but only if your content strategy puts your answers at the top of those search results. It's a simple and powerful equation that produces growth and success: They Ask, You Answer. Using these principles, author Marcus Sheridan led his struggling pool company from the bleak depths of the housing crash of 2008 to become one of the largest pool installers in the United States. Discover how his proven strategy can work for your business and master the principles of inbound and content marketing that have empowered thousands of companies to achieve exceptional growth. They Ask, You Answer is a straightforward guide filled with practical tactics and insights for transforming your marketing strategy. This new edition has been fully revised and updated to reflect the evolution of content marketing and the increasing demands of today's internet-savvy buyers.